Имитационное моделирование случайных возмущений при решении задач параметрического синтеза танковых информационно-управляющих систем - Александрова, Татьяна Евгеньевна; Мазманишвили, Александр Сергеевич; Сидоренко, Анна Юрьевна (НТУ "ХПИ", 2016)
Проводится имитационное моделирование случайных возмущений при решении задач параметрического синтеза танковых информационно-управляющих систем. Предложена математическая модель, описывающая случайные внешние возмущения, которые действуют на танковые системы и агрегаты. Данная методика состоит в выборе параметров формирующих динамических звеньев и двумерных полей при использовании одномерных и двумерных «белых шумов». Синтезированы алгоритмы построения двухмерного вещественного нормального марковского поля второго порядка, любые ортогональные сечения которого являются стационарными случайными процессами Орнштейна –Уленбека. Смоделированы нормальные марковские поля нулевого и второго порядков, реализованные на плоской поверхности двух переменных при различных параметрах формирующих динамических звеньев.

It is carried out simulation of random disturbances in solving problems of parametric synthesis of tank information management systems. A mathematical model has been describing the random external disturbances which act on the Tank system and units. This technique consists in choosing parameters dynamically generated links and two-dimensional field using a one-dimensional and two-dimensional "white noise." The algorithms for generating random two-dimensional object on the plane are used for modeling the movement of vehicles and consideration of other problems, the solution of which is Markov random field of the second order. Algorithm is synthesized for constructing two-dimensional real normal Markov field of the second order any orthogonal cross-sections of which are stationary stochastic Ornstein – Uhlenbeck process. It is shown that the proposed approach allows the synthesis of Markov random fields of higher order. Normal Markov fields of zero, first and second order, realized on the flat surface of two variables, have been modeled. In this article a sequence have been of embedded algorithms for generating random object of normal Markov field synthesized in the second row, any cross section which is orthogonal, are stationary stochastic Ornstein – Uhlenbeck processes, which differential equations are second order or higher. In this article an algorithm describes to increase the order of the random object – normal Markov field, any orthogonal cross sections which are stationary random Ornstein – Uhlenbeck process. The procedure of set out in article simulation highest disturbances acting on the tank systems and units is to select the parameters forming the dynamic links and two-dimensional fields and the use of onedimensional and two-dimensional "white noise", the generation of which is carried out with the help of software packages.
The simulation of random perturbations in solving the problem of parametric synthesis tank management information systems
Keywords: случайный процесс; марковские поля; двумерный объект; процесс Орнштейна – Уленбека; генерирование случайных полей; simulation of random disturbances; random process; Markov field; two-dimensional object; generating of random fields